2018
DOI: 10.1016/j.jglr.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Lake Turkana, major Omo River developments, associated hydrological cycle change and consequent lake physical and ecological change

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 23 publications
1
73
0
Order By: Relevance
“…The integration of the land cover mapping with the data from the participatory mapping demonstrated that though a new suite of provisioning services are now more relied on, they are found in land covers (e.g., shrubland and wetlands) reducing in spatial extent ( Table 5). Satellite land cover mapping showed a loss of seasonally-inundated river-adjacent lakes, no longer replenished by the annual Omo River flood given the Gibe III dam [47]. Our analyses also highlight other long-term environmental changes affecting ES that were not predicted in a recent synthesis of social-ecological change in the region [46], namely a reduction in grassland and shrubland and increase in bare ground.…”
Section: Es Change In the Lower Omomentioning
confidence: 51%
See 2 more Smart Citations
“…The integration of the land cover mapping with the data from the participatory mapping demonstrated that though a new suite of provisioning services are now more relied on, they are found in land covers (e.g., shrubland and wetlands) reducing in spatial extent ( Table 5). Satellite land cover mapping showed a loss of seasonally-inundated river-adjacent lakes, no longer replenished by the annual Omo River flood given the Gibe III dam [47]. Our analyses also highlight other long-term environmental changes affecting ES that were not predicted in a recent synthesis of social-ecological change in the region [46], namely a reduction in grassland and shrubland and increase in bare ground.…”
Section: Es Change In the Lower Omomentioning
confidence: 51%
“…We found that between 2013 and 2018, ES supply and demand has changed drastically. In particular, communities reported the loss of riverine flood-retreat crop production, associated with the removal of the annual flood due to the Gibe III dam [44,47]. As a result, communities are now more dependent on rain-fed cultivation, and a range of other provisioning ES such as fodder for livestock, wild fruits, bushmeat and fish, but focus groups reported that many of these services are also becoming increasingly scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monthly Omo inflows were estimated using a water balance model (Avery, 2009;Avery, 2012;Avery & Tebbs, 2018), which uses lake level changes from radar altimetry to estimate Omo inflows after accounting for evaporative losses and other river inflows.…”
Section: Environmental Driversmentioning
confidence: 99%
“…Satellite altimetry data are a reliable proxy for in situ lake levels in ungauged waterbodies such as Lake Turkana (Avery, 2009;Avery & Tebbs, 2018;Velpuri, Senay, & Asante, 2012), and the G-REALM dataset has an accuracy of 3 -5 cm for large lakes (USDA, n.d.).…”
Section: Data Uncertainty and Validationmentioning
confidence: 99%